Marketing Implications of Information Society Privacy Concerns - Gheorghe ORZAN; Călin VEGHEŞ; Cătălin SILVESTRU; Mihai ORZAN; Ramona BERE (Revista de Management Comparat International)
Privacy has become over the last decade one of the foremost social concerns, since the arrival of cheap and ubiquitous surveillance of both online and offline behavior. The Internet has facilitated access to intimate user knowledge for both official and private agents and most of modern marketing strategies are based on a wealth of personal user data used to target its specific needs and expectations, a process that has its obvious pros and cons, which have been heavily debated intensively in both academic and social venues. Our paper attempts to uncover some of the most important privacy-related aspects of modern consumers, with a focus on their preferences for information access, marketing messages exposure, attitudes towards disclosing, capturing, processing and employment of their personal data, as well as their attitude towards various forms of media associated with our modern Information Society.